Personal beginnings and institutional endings in spiritualism - Tomlinson, Matt (The Australian journal of anthropology, 2022)
In the religious movement known as Spiritualism, a medium's task is to provide evidence that there is no such thing as death. Human existence is defined by Spiritualists in terms of continual spiritual progress rather than stark beginnings and endings, although converts do tell vivid stories of the moment they realised Spiritualism's truth. The movement changed over decades as mediums turned their attention from physical to mental manifestations of spiritual presence. Mediumship has remained popular in public culture, but as an institution Spiritualism has declined in prominence to the point where many members of the movement now join it as converts and worry about the closure of churches. In this article, I juxtapose personal and institutional beginnings and endings to show their interrelation, with people's senses of radical newness and progress cultivated in the context of perceived institutional decline.